The foundations of research - Grix, Jonathan (New York Palgrave Macmillan, 2004)
This book offers advanced undergraduate and postgraduate students with an accessible introduction to the foundations of research in the human sciences. It covers the tools, terminology and research perspectives that researchers and students will need to know in order to engage in academic debate, and to successfully complete their long essays, dissertations and theses. A particular strength of this volume is its style: It is written to the student as opposed to just for them. Language is kept as clear as possible, especially when describing the basic assumptions upon which all research is built.